Design of a Field Mill Device for Measuring the High Voltage DC Fields - Rehman, M. (Institute of Electrical and Electronics Engineers Inc., 2021)
This paper presents the design, development and realization of a field mill for accurately measuring the DC field. In this research study, a typical capacitor, comprising of one fixed electrode and another rotating electrode is used. A controlled DC motor based on PWM (Pulse Width Modulation) technique is used which drives the rotating electrode of the capacitor. The ATmega8 microcontroller is employed, mainly, for analog to digital conversion, PWM generation and for reading the output of the photoelectric sensor. The programming of the ATmega8 microcontroller is done in C-language; WinAVR tool is used for the programming. The performance of the developed field mill is analyzed by creating the DC electric field in the laboratory environment with the help of parallel plate capacitor. A regulated HVDC supply setup is also built for parallel plate capacitor. The developed field mill was tested under positive as well as negative polarity. The proposed field mill is portable, it can be used anywhere to measure the DC field. The development details, mechanical, electrical and electronic components used, and the experimental results are presented in this paper. The overall results show that the developed field mill device can measure the DC field up to the range of ± 65 kV/m, with standard deviation of only ± 2.42. © 2021 IEEE.